2006
DOI: 10.1111/j.1460-9568.2006.04730.x
|View full text |Cite
|
Sign up to set email alerts
|

Spike‐timing‐dependent plasticity at resting and conditioned lateral perforant path synapses on granule cells in the dentate gyrus: different roles of N‐methyl‐d‐aspartate and group I metabotropic glutamate receptors

Abstract: We examined the mechanisms underlying spike-timing-dependent plasticity induction at resting and conditioned lateral perforant pathway (LPP) synapses in the rat dentate gyrus. Two stimulating electrodes were placed in the outer third of the molecular layer and in the granule cell layer in hippocampal slices to evoke field excitatory postsynaptic potentials (fEPSPs) and antidromic field somatic spikes (afSSs), respectively. Long-term potentiation (LTP) of LPP synapses was induced by paired stimulation with fEPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 64 publications
4
33
0
Order By: Relevance
“…We previously reported that associative LTP can be induced by a pairing protocol in hippocampal CA1 and lateral perforant pathway [13,14]. We have also demonstrated that results obtained with the extracellular recording technique are compatible with those obtained with the whole-cell recording technique, in which LTP of the weak pathway is induced by pairing it with post-synaptic spiking.…”
Section: Discussionsupporting
confidence: 86%
“…We previously reported that associative LTP can be induced by a pairing protocol in hippocampal CA1 and lateral perforant pathway [13,14]. We have also demonstrated that results obtained with the extracellular recording technique are compatible with those obtained with the whole-cell recording technique, in which LTP of the weak pathway is induced by pairing it with post-synaptic spiking.…”
Section: Discussionsupporting
confidence: 86%
“…If distal synaptic inputs are activated within a narrow time window of less than ϳ10 ms, they will sum up and effectively depolarize the dendritic membrane potential. As a consequence, activation of dendritic voltage-dependent Ca 2ϩ channels (Blaxter et al, 1989) and NMDA receptors (Lin et al, 2006) will depend on highly coincident synaptic potentials.…”
Section: Dendritic Coincidence Detectionmentioning
confidence: 99%
“…This was essentially independent of whether synapses were placed on the dendritic shaft or on spines, because the electrical properties of synaptic spines attenuated the dendritic EPSPs by Ͻ10%. This would indicate that few synapses activated within a narrow time window of Ͻ10 ms may be able to relieve voltage-dependent Mg 2ϩ block and trigger local dendritic Ca 2ϩ influx via NMDA receptors, known to be important for the induction of synaptic plasticity (Golding et al, 2002;Lin et al, 2006).…”
Section: Dendritic Coincidence Detectionmentioning
confidence: 99%
“…Since ERK activation is essential for the induction of certain forms of LTP at cortical synapses (Impey et al, 1999;Lin et al, 2003Lin et al, , 2006, we tested whether ERK-dependent LTP could be induced by high-frequency stimulation (HFS) at PBA-CeAC synapses in slices from normal mice and whether LTP induction might share common mechanisms with induction of PKC-ERKdependent potentiation by PDA and with postsynaptic enhancement of PBA-CeAC EPSCs in AIMP animals. As shown in Figure 8 A (squares), after application of three trains of HFS at 100 Hz to slices from normal mice, the PBA-CeAC EPSP was significantly potentiated to 191 Ϯ 30% of baseline (n ϭ 9 cells tested, p Ͻ 0.05, paired t test), and potentiation lasted for at least 30 min.…”
Section: Induction Of Nmdar-pkc-erk-dependent Ltp Of Pba-ceac Epscsmentioning
confidence: 99%
“…These plastic changes in synaptic function in the pain-related CNS areas are considered to be a part of the cellular mechanisms underlying the development of central sensitization in chronic pain (Ji et al, 2003). At some cortical synapses, LTP induction requires activation of extracellular signal-regulated kinase (ERK) (Impey et al, 1999;Giovannini et al, 2001;Lin et al, 2003Lin et al, , 2006. Since a biochemical hallmark of chronic pain is increased levels of phosphorylated ERK (pERK) in the DH (Ji et al, 1999;Garry et al, 2005;Wei et al, 2006) (for review, see , it is likely that ERK activity triggered by repeated and excessive noxious stimuli might induce LTP of nociceptive inputs onto DH neurons, thereby resulting in central sensitization.…”
Section: Introductionmentioning
confidence: 99%